Mythical Marketing – The Holy Grail of Today's Ueber-Brands - Wolfgang Schaefer; J. P. Kuehlwein (Marketing Review St.Gallen, 2016)
Storytelling has become the hot topic in marketing for many reasons. Truly successful marketers however try not to just build their brands around stories but imbue and elevate them through myths. In the course of the past four years, the authors have analyzed more than 100 cases across all price tiers and product categories and spoke to an uncounted number of experts and practi-tioners. The result: Today's strongest and most price-insensitive players use meta-narratives to give their brands depth and gravitas while at the same time catapulting themselves to superior heights and long-lasting stature. Most apply one of two strategies: They try to 'reach beyond', allowing their targets to feel as if they were connecting to a higher truth. Or they use the 'guiding power' of myths, projecting archetypes that inspire and which many can aspire to, no matter their realities.
Keywords: 650